Cognitive And Neuroprotective Effects of Vernonia amygdalina in scopolamine-induced Memory impaired Rats. (Nigerian Journal of Physiological Sciences, 2024)
Cognitive impairment is largely associated with functional and structural loss in the brain of Alzheimer’s disease (AD) models, and scopolamine has been successfully used to mimic these deficits in rodents. The cost and side effects of drugs presently used for the treatment of AD-related cognitive impairment have prompted research into alternative products, especially natural ones with high antioxidant capacity, since oxidative stress is a major pathophysiology associated with AD. The current study evaluated the cognitive and neuroprotective effects of Vernonia amygdalina (VA) on scopolamine-induced cognitive impairment in rats. Thirty-five male rats, randomly divided into seven groups (n = 5), were used. Group 1 served as the control and received distilled water. Groups 2 and 3 received Vernonia amygdalina, VA (50 and 100 mg/kg, respectively) per orally (p.o.). Group 4 received 1 mg/kg scopolamine SC (i.p.). Groups 5, 6, and 7 received pretreatment with either VA 50 mg/kg, VA 100 mg/kg, or Donepezil, DP (1 mg/kg), and then in combination with SC (1 mg/kg). The animals were subjected to memory tasks using the Morris water maze (MWM) and novel object recognition tasks (NORT) and sacrificed on day 14, after which their brains were isolated for biochemical and histological studies. The study showed that during MWM and NORT, spatial and non-spatial recognition memories, which were respectively impaired in the SC group compared to the control group, were reversed in the VA pretreatment groups. Scopolamine injection caused significant decreases in superoxide dismutase and catalase levels and an increase in malonaldehyde (MDA) levels in group 4 compared with the control group. Pretreatments with either VA or DP, however, caused a significant increase in the SOD and catalase levels and a decrease in the MDA level compared with the SC group. Histological studies revealed that VA was more potent in protecting the brain against SC-induced neurodegeneration and morphological alterations in the hippocampus and prefrontal cortex. Findings of this study suggest that VA attenuates scopolamine-induced cognitive deficits via inhibition of oxidative stress and neuronal degeneration and enhancement of cognition in the brains of rats.